THE INFLUENCE OF INTERACTIVE READ ALOUD STRATEGY (IRAS) AND MOTIVATION TOWARDS THE NINTH GRADE STUDENTS’ ACHIEVEMENT IN READING NARRATIVE TEXT AT STATE HIGH SCHOOL 6 OF PALEMBANG - Nur Azizah (Universitas PGRI Palembang, 2019)
AbstractThis thesis is conducted in experimental group with the total sample is 32 students of eleventh grade students of SMP N 6 Palembang. It inquiry of the influence of IRAS and Learning Motivation toward Reading Achievements. The problem of this study is to find out the significance average score and motivation between IRAS and Conventional Technique. Due the interpretation of this study, it is found that: (1) there was significant difference in reading comprehension achievement between the ninth grade students who have high motivation and those who have low motivation taught by using Interactive Read Aloud Strategy, it was found that the result was 0.01 it means that lower than significant level (0.05), (2) there was significant difference in reading comprehension achievement between the ninth grade students who have high motivation and those who have low motivation taught by using Conventional method since the result was 0.01 and it means that lower than significant level (0.05), (3) there was significant difference in reading comprehension achievement between students who have high motivation and those who have low reading motivation taught by using Interactive Read Aloud Strategy (IRAS) and Conventional Method since the result was 0.00 and it means that lower than significant level (0.05), and (4) there was an interaction effect of Interactive Read Aloud Strategy (IRAS) and motivation on reading comprehension achievement of the ninth grade students at State Junior High School 6 of Palembang since the significant was lower (0.04) than significant level (0.05). Based on the result, the writer concludes that IRAS and motivation gave the significant influence for student’s narrative Reading achievement since there was a significant improvement before and after taught IRAS technique.Keywords: IRAS, Reading and Motivation